A diuranium carbide cluster stabilized inside a C80 fullerene cage - Xingxing Zhang (Nature Portfolio, 2018)
While metal–carbon double bonds are common in transition metal chemistry and catalysis, unsupported uranium–carbon double bonds remain highly challenging to prepare. Here, the authors stabilize and characterize a U=C=U cluster containing unusually short, unsupported double bonds inside an I h(7)-C80 fullerene cage.